2010
DOI: 10.3945/ajcn.2009.28625
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and acidic oligosaccharides in preterm infants: a randomized, double-blind, placebo-controlled trial

Abstract: Enteral supplementation of (SC)GOS/(LC)FOS/AOS does not significantly reduce the risk of serious infectious morbidity in preterm infants. However, there was a trend toward a lower incidence of serious infectious morbidity, especially for infections with endogenous bacteria. This finding suggests a possible beneficial effect that should be evaluated in a larger study. This trial was registered at isrctn.org as ISRCTN16211826.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
2
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 33 publications
4
62
2
15
Order By: Relevance
“…The formulation of enteral probiotics and their most effective dosages also needs further study. (22,43) In a meta-analysis, Deshpande et al confirmed the beneficial effects of probiotics against fatal NEC and neonatal sepsis and recommended its routine use. (44) Antioxidants are involved in several immune response phases, such as phagocytosis, cytokine production, cellmediated responses and immunoglobulin production; these substances are therefore considered immunonutrients.…”
Section: Nutrient or Immune Nutrient Offermentioning
confidence: 99%
“…The formulation of enteral probiotics and their most effective dosages also needs further study. (22,43) In a meta-analysis, Deshpande et al confirmed the beneficial effects of probiotics against fatal NEC and neonatal sepsis and recommended its routine use. (44) Antioxidants are involved in several immune response phases, such as phagocytosis, cytokine production, cellmediated responses and immunoglobulin production; these substances are therefore considered immunonutrients.…”
Section: Nutrient or Immune Nutrient Offermentioning
confidence: 99%
“…The sample size of 113 infants was based on the sample size calculation for the primary outcome of the main trial (serious infectious morbidity) (21). Normally distributed and nonparametric data are presented as means Ϯ SD and medians (ranges).…”
Section: Subjectsmentioning
confidence: 99%
“…Protocol guidelines for the introduction of parenteral and enteral nutrition followed current practice at our NICU. Nutritional support was administered as previously described (21,22). For each infant in the study, a feeding schedule was proposed based on BW and our guidelines.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations